Pathogenic parasites in vegetables in the Middle East and North Africa: Occurrence of Ascaris eggs and Giardia cysts, and epidemiological implications. (January 2023) - Amahmid, Omar; El Guamri, Youssef; Rakibi, Youness; Ouizat, Saadia; Yazidi, Mohamed; Razoki, Bouchra; Kaid Rassou, Khadija; Achaq, Hanane; Basla, Safia; Zerdeb, Mohamed Amine; El Omari, Meriyam; Touloun, Oulaid; et al.
Abstract: Parasitic diseases are a major health problem in many developing countries. The consumption of contaminated fresh vegetables can play a crucial epidemiological role in the transmission of parasitic foodborne diseases including ascariasis and giardiasis. This review explored the occurrence of the pathogenic parasites Ascaris and Giardia on vegetables collected from markets, street vendors, groceries, and farms in the Middle East and North African countries. Electronic databases including PubMed, Scopus, Web of Science, Google Scholar, ScienceDirect Scopus, ResearchGate and other sites, were searched for available data. Overall, 11 066 samples of 32 vegetable varieties, were investigated. The pooled prevalence of Giardia in vegetables reached 8.5% (range 0–16.9%) while that of Ascaris was 8% (range 0–27.7%). Ascaris and Giardia levels in crops ranged from 0.2 to 78 eggs/kg and 1–253 cysts/kg, respectively. The prevalence and concentrations of parasites varied depending on the type of vegetables, with the highest levels in leafy vegetables. The persistence of pathogenic parasites cysts and eggs in crops was addressed based on available data. The occurrence of pathogenic parasites in food crops implies potential health risks for farmers, produce handlers, and consumers. Suggested measures for risk mitigation include good hygiene practices, the use of clean irrigation water, and crops being appropriately washed and cooked before consumption.